Sindicalismo e meio ambiente: a participação da Central Única dos Trabalhadores nas Conferências Eco 92 e Rio +20 - Marques, Viviane Bassi dos Reis [UNESP] (2014)
Discourses about the social and environmental impacts , seen as consequences of the capitalist development model , are increasingly present on businesses, government, NGOs , and social movements of all kinds. However it is not homogeneous discourse , since each social actor maintains specific guidelines , in accordance with their interests . This study has as a research input from environmental theme in the Central Workers Union (CUT ) . The aim is to reveal through the speeches of union leaders , interests, motivations , practices and union strategies , mapping its allies , partners , as well as insertion of foreign exchange in the trade union world social spaces . The research hypothesis is based on the idea that trade unions after the restructuring process occurred in companies in the 90s , changed their strategies for integration and fight, aiming to maintain his performance opposite to the changes in the capital ratio / work . The discourse of sustainable development and environmental responsibility , given by the union , may be part of the new union strategies , targeting the insertion of central important in new social spaces , the search for legitimacy and by introducing and defending trade union agendas that relate labor and environmental . The empirical cut is defined by two important events around the environmental issue: the United Nations Conference on Enviroment and Development, the Eco 92, and the United Nations Conference on Sustainable Development, the Rio +20. This is a research inspired by economic sociology, environmental sociology and brought concepts of Pierre Bourdieu and Mary Douglas